The effect of subliminal priming on team trust: The mediating role of perceived trustworthiness - Cai, Jie; Wu, Rongxiu; Zhang, Jingyu; Sun, Xianghong (Frontiers in Psychology, 2023)
The present study aimed to explore the effect of subliminal priming on team trust and the mechanism through the mediating role of perceived trustworthiness. 144 participants were asked to complete a lexical decision task which was embedded the “trust” or “suspicion” Chinese words as the subliminal stimuli, then they played a public good game and evaluated perceived trustworthiness of the team. The results of the study showed that subliminal stimuli had a significant effect on team trust (β = - .99, 95% CI = [-1.64, -.33]). Perceived trustworthiness was found to have a significant mediating effect between priming condition and team trust (β = -.35, 95% CI = [-.72, -.02]). The current study revealed the underlying mechanism through which subliminal priming techniques influence team trust, and informed efforts through altering perceived trustworthiness.